Dehydration of potato slices following brief dipping in osmotic solutions: Effect of conditions and understanding the mechanism of water loss. Issue 7 (19th May 2019) - Mokhtar, Wan Mohd Fadli Wan; Ghawi, Sameer Khalil; Niranjan, Keshavan
Abstract: A novel variant of osmotic dehydration, named here as postdipping dehydration—where a material is dipped in a salt or sugar solution for a very short time followed by simple exposure to ambient conditions was explored with the aim of lowering water content of potato slices but at the same time not gain a high level of sugar/salt. The rate of water loss, which was rapid initially, was found to approach equilibrium. This article also explored whether the water loss process could subsequently be kick started once again, by employing a multistage process, where each stage consisted of osmotic solution dipping followed by ambient holding of the potato slices that had reached equilibrium in the earlier stage. Water loss values comparable to conventional osmotic dehydration could be achieved thus, but with significantly lower overall solid gain (<50%)—which can potentially yield a significantly healthy product option.